Future Time Perspective and the Achievement of Optimal Best: Reflections, Conceptualizations, and Future Directions for Development - Phan, Huy P.; Ngu, Bing H.; McQueen, Kelvin (Frontiers in Psychology, 2020)
Abstract Time is an interesting concept. For some cultural groups, time is an entity that only exists here and now, whereas for others it is perceived as being linear, emphasizing a person’s past, present, and future. Many of us, living in the ‘present moment’, may anticipate and project future goals, dreams, hopes, and ambitions for accomplishment. Indeed, from a positive point of view, future orientations are healthy and may direct focus, instill motivation and persistence, and mobilize effort expenditure. Existing research has provided empirical evidence to support the promotion and encouragement of positive future time orientation. A person’s positive future time orientation, for example, may entail her goal to successfully complete the annual cross-city marathon. Indeed, from an educational point of view, the study of time is a noteworthy feat for advancement, given that this construct may guide and direct a student to consider his/her academic and/or non-academic future. One notable inquiry for consideration, in this case, relates to the importance of timespan – that is, how ‘much’ into the future should one consider? There is a difference, say, between a timespan that scopes a 6-month period as opposed to a timespan that scopes a 2-year period. By the same token, over the past few years, we have been interested in an inquiry that delves into the nature of optimal best – for example, what is it that facilitates and/or causes a person to achieve optimal best in a subject matter? Our theory of human optimization, consolidated and recently published in Frontiers in Psychology, provides an in-depth theoretical account of an underlying process, which we postulate could explain the achievement of optimal best. Optimization, in this case, is intricately linked to a person’s achievement of optimal best. We rationalize that within the context of academic learning, cognitive complexity of a subject matter could serve as an important source of motivation in the anticipation and projection a student’s extended future timespan. In this analysis, the extremely complex nature of a learning tasks or a suite of tasks may compel a longer future timespan for successful completion.